Preparation and characterization of polyaniline-Cu-Ni nanocomposite thin film sensors for detection of pathogenic Leptospira - Abdullah, Huda; Suppiah, Aravintha Ram; Yu, Jion Wei; Jurait, Jamal; Yahya, Iskandar; Kamal, Noorfazila; Mohammad Naim, Norshafadzila; Bejo, Siti Khairani; Othman, Mohd Hafiz Dzarfan; Fen, Yap Wing; Yuliarto, Brian; Ahmad, Md Fauzi; et al. (Elsevier, 2023)
This research was conducted to study on PANI-Cu-Ni nanocomposite thin film sensors for Leptospira detection. PANI-Cu-Ni nanocomposite was deposited onto glass substrate by spin-coating technique. The morphological and structural properties of the thin films have been analysed using atomic force microscopy (AFM), field emission scanning electron microscopy (FESEM) and energy dispersive X-ray (EDX). Leptospira bacterium existence was determined by sensitivity and selectivity tests through I-V measurement and EIS analysis. From the result, FESEM and EDX investigations showed the abnormality of nanoparticle thin film ranging in size from 40 to 60 nm in the existence of metal in substrates, revealing the engagement between the microbe and thin film surface. PANI-Cu-Ni nanocomposite thin films were successful and effective in detecting the existence of Leptospira in water. PANI-Cu0.6-Ni0.4 thin films demonstrated greater sensitivity for the identification of Leptospira. From the sensitivity plot, the increasing of Ni has decreased the sensitivity performance.